Teacher Training on Healthy Canteen Improves Knowledge and Attitude of Primary School Student - Ana Yuliah Rahmawati; Kun Aristiati Susiloretni; Fitriani; Arina Nurul Ihsani (Journal of Health Education, 2026)
Background: School age is one of the periods that experience rapid growth and development and are highly vulnerable to nutritional problems due to poor eating habits influenced by their school environment. Nutrition education interventions in schools are essential to improve knowledge, attitudes, and behaviors related to healthy eating among students and teachers. This study aimed to evaluate the effectiveness of nutrition education interventions using videos and leaflets in improving the knowledge, attitudes, and practices of students and teachers, regarding healthy snack selection in elementary schools.Methods: This quasi-experimental study with a non-randomized one group pre-post test design was conducted in two elementary schools in Semarang, involving students and teachers. Data were collected through nutrition education interventions using videos and leaflets, with knowledge, attitudes, and practices measured before and after the intervention.Results: There is an effect of nutrition education on students' knowledge and attitude in choosing healthy snacks (p<0.001), the effect of nutrition education on teachers' attitude choosing healthy snacks in both groups (p=0.027).Conclusion: The results showed that nutrition education interventions using videos and leaflets effectively improved students’ knowledge and attitudes toward healthy snack choices, and also enhanced attitudes among teachers. However, the intervention had limited effect on improving teachers’ knowledge, highlighting the need for more targeted and interactive approaches, especially for adults